Supplementary Figure 22. from Clinicopathologic, Genomic, and Immunophenotypic Landscape of ATM Mutations in Non–Small Cell Lung Cancer - Biagio Ricciuti (14951247) (2025)
Supplementary Figure 22. Proportion of (A) tumor, (B) non-tumor, and (C) total PD-L1+ cells in ATMMUT and ATMWT NSCLCs.